Human adenovirus type 3 restores pharmacologically inhibited exosomal cargo in lung carcinoma cells - Ayodeji O. Ipinmoroti; Rachana Pandit; Brennetta J. Crenshaw; Brian Sims; Qiana L. Matthews; Qiana L. Matthews (Frontiers in Pharmacology, 2024)
Introduction: Drug repurposing is fast growing and becoming an attractive approach for identifying novel targets, such as exosomes for cancer and antiviral therapy. Exosomes are a specialized class of extracellular vesicles that serve as functional mediators in intercellular communication and signaling that are important in normal physiological functions. A continuously growing body of evidence has established a correlation between the abnormal release of exosomes with various viral disease pathologies including cancer. Cells that are virus-infected release exosomes known to influence the process via the loading and transfer of viral components, such as miRNA, small (s) RNA, DNA, and proteins. Inhibition of exosome release may abate the spread and severity of viral infection, thus making exosomes an attractive target for antiviral therapies. We previously demonstrated the pharmacological inhibition of exosomes.Methods: Herein, we used a cell-based assay to determine the effect of Human adenovirus type 3 (HAdV3) on the exosome inhibition process by azole and Heparin derivatives. HAdV3-infected cells were treated with two concentrations of each inhibitor at different time points.Results: HAdV3 activities led to increased total sRNA, DNA, and exosome particle concentrations via particle tracking in the presence of Climbazole and Heparin relative to uninfected exosomes. In addition, there was an increased expression of classical markers such as ALG-2 interacting protein X (ALIX), and tetraspanin (CD63), (p < 0.05) and upregulated transcription factor interferon regulatory factor (IRF) 8 in the presence of HAdV3 after 24 hours (h) of treatment. Whereas higher concentrations of Climbazole and Heparin sodium salt were found to inhibit total exosome protein (p < 0.001) and exo-RNA (p < 0.01) content even in the presence of HAdV3 relative to infected exosomes only. Activities of HAdV3 in the presence of selected inhibitors resulted in the positive regulation of exosome related DNA damage/repair signaling proteins. Blocking exosome secretion partially obstructed viral entry. Immunological studies revealed that HAdV3 fiber protein levels in A549 cells were reduced at all concentrations of Climbazole and Heparin and both multiplicities of infections (p < 0.001).Discussion: Our findings suggest that while HAdV may bolster inhibited exosome content and release when modulating certain activities of the endosomal pathway mediators, HAdV entry might be constrained by the activities of these pharmacological agents.